Retrograde Ureteric Stents via an Ileal Conduit. (7th April 2011) - Jack, Andrew; Burbridge, Brent E.
Abstract : Patients having undergone pelvic exenteration with urinary diversion can present with short- and long-term complications such as ureteral strictures, anastomotic leakage, calculi, or fluid collections (abscess, urinoma, lymphocele, or hematoma). A dehiscence resulting in a perineal urinary fistula is an uncommon late complication of urinary diversion surgery; surgical treatment for this complication is less desirable because of postsurgical or radiation-induced pelvic changes that can occur. As a result, nephrostomy or antegrade stenting of the kidneys is more viable. Retrograde ureteric stent insertion is discussed in relation to a patient suffering from ileal conduit dehiscence. The presence of these stents probably helped diminish the potential for complications during subsequent nephrostomy tube insertion.